Patient Satisfaction Analysis at the Inpatient Installation of Ibnu Sina Hospital, Makassar City - Nasrah Wati (CV, Akira Java Bulu, 2025)
Quality health services are health services that can satisfy every service user according to the average level of satisfaction of the population and its implementation in accordance with the code of ethics and service standards that have been set. Therefore, researchers are interested in conducting research at Ibnu Sina Hospital, Makassar City, to determine the picture of inpatient satisfaction at Ibnu Sina Hospital, Makassar City. This study uses a quantitative research type with a descriptive design. The population in this study was 3103 patients and a sample of 354 respondents obtained by stratified random sampling using inclusion criteria. The results of the study showed that all respondents had good opinions about the reliability variable (100%), responsiveness who had good opinions were (98.3%), while less good (1.7%), the assurance dimension who had good opinions (99.2%), while less good (8%), the direct evidence dimension who had good opinions was (97.5%), while less good (2.2%), the empathy dimension who had good opinions (97.5%), while less good (2.5%), and patient satisfaction, the most had good opinions, namely 354 respondents. To improve patient satisfaction with services, cooperation from all parties is needed, health workers improve their performance, hospitals improve the quality of services and existing human resources, the Health Office makes a policy related to health worker services, both medical and non-medical, in all hospitals in South Sulawesi. And further researchers should use different variables from the variables in this study.